HUBUNGAN ANTARA KESTABILAN EMOSI DENGAN KONTROL DIRI SISWA KELAS XI DI SMAN 1 KERUAK TAHUN PELAJARAN 2024/2025 - Maulana, Alan Kurnia; Ahmad, Hariadi; Zainuddin, M. (Yayasan Al-Amin Qalbu, 2025)
Emotional stability refers to not over-expressing emotions, as excessive emotional expression can harm both physical and mental health. Meanwhile, self-control is an individual's ability to sensitively read situations, understand their own capabilities and the environment, and manage factors influencing student behavior in various situations. Students with good emotional stability tend to be able to control themselves, and vice versa. The research question in this study is whether there is a relationship between emotional stability and self-control among Grade XI students at SMAN 1 Keruak for the 2024/2025 academic year. The purpose of this study is to determine the relationship between emotional stability and self-control among at SMAN 1 Keruak in the 2024/2025 academic year. The data collection technique in this study uses a questionnaire with a Likert scale as the primary data source and documentation as the supporting data source. This study uses a quantitative correlational method with a population and sample of 27 students in grade XI at SMAN 1 Mataram. Data analysis of the research results used inferential statistics, specifically the Spearman rank correlation test. The research findings revealed a strong and significant relationship between Emotional Stability and Self-Control Among Grade XI Students at SMAN 1 Keruak for the 2024/2025 Academic Year, as indicated by the Spearman rank correlation test result of 0.509.